Nanomaterials versus ambient ultrafine particles: an opportunity to exchange toxicology knowledge - Stone, Vicki (2017)
BACKGROUND: A rich body of literature exists that has demonstrated adverse human health effects following exposure to ambient air particulate matter (PM), and there is strong support for an important role of ultrafine (nanosized) particles. At present, relatively few human health or epidemiology data exist for engineered nanomaterials (NMs) despite clear parallels in their physicochemical properties and biological actions in in vitro models. OBJECTIVES: NMs are available with a range of physicochemical characteristics, which allows a more systematic toxicological analysis. Therefore, the study of ultrafine particles (UFP, <100 nm in diameter) provides an opportunity to identify plausible health effects for NMs, and the study of NMs provides an opportunity to facilitate the understanding of the mechanism of toxicity of UFP. METHODS: A workshop of experts systematically analyzed the available information and identified 19 key lessons that can facilitate knowledge exchange between these discipline areas. DISCUSSION: Key lessons range from the availability of specific techniques and standard protocols for physicochemical characterization and toxicology assessment to understanding and defining dose and the molecular mechanisms of toxicity. This review identifies a number of key areas in which additional research prioritization would facilitate both research fields simultaneously. CONCLUSION: There is now an opportunity to apply knowledge from NM toxicology and use it to better inform PM health risk research and vice versa.